ATRT-22. SWI/SNF COMPLEX HETEROGENEITY RELATES WITH POLYPHENOTYPIC DIFFERENTIATION AND THE IMMUNE MICRO ENVIRONMENT IN RHABDOID TUMORS. Issue 2 (22nd June 2018) - Venneti, Sriram; Panwalkar, Pooja; Chung, Chan; Pratt, Drew; Martinez, Daniel; Bayliss, Jill; Paran, Christopher; Hawes, Debra; Pawel, Bruce; Judkins, Alexander
Abstract: Malignant rhabdoid tumors (MRT), including central nervous system (CNS) Atypical Teratoid / Rhabdoid Tumors (AT/RT) and extra CNS (eCNS) MRT, are aggressive cancers characterized by loss of SMARCB1, a core component of the SWI/SNF chromatin-remodeling complex. Histopathologically, MRTs are characterized by polyphenotypic differentiation that varies from tumor to tumor. Because the SWI/SNF complex regulates differentiation we hypothesized that the SWI/SNF complex would exhibit heterogeneity in MRTs. We first characterized the SWI/SNF complex in developing human brain. SMARCB1 expression was highest in the cerebellum compared to hemispheric regions and remained so throughout development. In contrast, many subunits of the SWI/SNF complex were down regulated after cerebellar development. In MRTs we discovered that the SWI/SNF complex subunits showed marked differences between AT/RTs and eCNS MRTs. In eCNS MRTs high ACTL6A and ACTL6B expression was associated with neuronal differentiation while tumors with low ACTL6A and ACTL6B showed epithelial and mesenchymal differentiation. In AT/RTs there was marked heterogeneity in members of the PBAF complex including ARID2, BRD7 and PBRM1. Tumors with high PBAF expression were associated with worse prognosis, increased metastasis and cell cycle deregulation. Of the PBAF components, tumors with low PBRM1 showed a better prognosis and were associated with increased cytotoxic lymphocytes in their microenvironment. Our data demonstrate that MRTs exhibit heterogeneity in the SWI/SNF complex that may contribute to the polyphenotypic differentiation characteristic of these tumors, and which may have implications in understanding the biology, prognosis and development of immunotherapeutic approaches to these tumors.